The effectiveness of using My Intelligent Buzzlamp in the teaching and learning process - Wahab Herman Nordiadi bin Abd; Nasir Nurul Nisa binti Mohd (E3S Web of Conferences, 2024)
My Intelligent Buzzlamp is a teaching aid tool designed to assist students during practical sessions for examining vehicle electrical systems. This tool facilitates the examination process by providing light and audible beeps as indications of fuse status. This examination process is crucial when issues arise, such as non-functional audio systems or vehicle electronic components. Visual impairment, especially among older mechanics or those facing glare-related problems, as well as difficulties in using a multimeter for examination, are challenges addressed by this innovation. The use of this tool is highly straightforward, where students only need to connect the alligator clip to the battery terminal and touch the tip of the innovation to the fuse terminal. If the fuse is functional and in good condition, the tool will light up and emit a beeping sound. In conclusion, this innovation has succeeded in assisting students in carrying out practical tasks more easily and effectively, conserving labour and space, and reducing the duration of execution.